2020
DOI: 10.1039/d0ra05690a
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of MOFs/GO composite for corrosion resistance application on carbon steel

Abstract: Two unreported metal–organic frameworks [Cu(6-Me-2,3-pydc)(1,10-phen)·7H2O]n (namely Cu-MOF) and [Mn2(2,2′-bca)2(H2O)2]n (namely Mn-MOF) were synthesized and characterized. Cu-MOF and Mn-MOF all can form a three-dimensional structure.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 64 publications
0
18
0
Order By: Relevance
“…The coordination bond Co−O bond length is between 0.20427 to 0.21420 nm, the Co−N bond length is 0.21648 nm, and the reported Co−X (X=O, N) bond length (between 0.1995 to 0.2148 nm) range Unanimously [25] . The bond angle O−Co‐X (X=O, N) is between 83.80(6) to 174.73(6)°, which are all within the normal range [26,27] . Co 2+ is the metal node of Co‐MOF 2 , deprotonated ligand (6‐Me‐2,3‐pydc) 2− is connected to each other as a linker, which are connected to each other to form an infinitely extending one‐dimensional chain structure (Figure 2b).…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…The coordination bond Co−O bond length is between 0.20427 to 0.21420 nm, the Co−N bond length is 0.21648 nm, and the reported Co−X (X=O, N) bond length (between 0.1995 to 0.2148 nm) range Unanimously [25] . The bond angle O−Co‐X (X=O, N) is between 83.80(6) to 174.73(6)°, which are all within the normal range [26,27] . Co 2+ is the metal node of Co‐MOF 2 , deprotonated ligand (6‐Me‐2,3‐pydc) 2− is connected to each other as a linker, which are connected to each other to form an infinitely extending one‐dimensional chain structure (Figure 2b).…”
Section: Resultsmentioning
confidence: 95%
“…[25] The bond angle OÀ Co-X (X=O, N) is between 83.80(6) to 174.73(6)°, which are all within the normal range. [26,27] Co 2 + is the metal node of Co-MOF 2, deprotonated ligand (6-Me-2,3-pydc) 2À is connected to each other as a linker, which are connected to each other to form an infinitely extending one-dimensional chain structure (Figure 2b).…”
Section: Crystal Structurementioning
confidence: 99%
“…Meanwhile, it has been reported that Cu-MOF and Mn-MOF composites were able to protect carbon steel from corrosion at 3.5 wt% NaCl solution. 23 It is noted that ZnO@zeolite imidazole framework-8 (ZnO@ZIF-8) core–shell materials have been frequently investigated as chemical gas sensors to selectively detect acetone 24–26 and formaldehyde, 27 while very rare attention has been paid to them as electrochemical sensors. 22…”
Section: Introductionmentioning
confidence: 99%
“…It is therefore considered a very promising support for MOF composites [48][49][50]. GO/MOF composites expand the versatility of MOFs and have resulted in innovative applications in various fields [50][51][52][53][54], GO/MOF composites materials have been synthesized and widely used in various fields (Fig. 1).…”
Section: Introductionmentioning
confidence: 99%